Pentingnya Peranan Pemerintah Daerah dalam Penyelenggaraan Pemilihan Umum - Maninggesa, Suwardi (AHKAM, 2022)
In the Indonesian state, the Constitution guarantees the sovereignty of the people, this is contained in article 2 paragraph (2) of the 1945 Constitution which states that "Sovereignty is in the hands of the people and implemented according to the Constitution" then this is contained in the 4th Pancasila precept which reads "Populist led by wisdom in representative deliberations" then its implementation is carried out in Law Number 7 of 2017 concerning General Elections, Article 1 explains that General Elections, hereinafter referred to as elections, are a means of ratkyat sovereignty to elect members of the People's Legislative Assembly, members Regional Representative Council, President and Vice President, and to elect members of the Regional People's Legislative Assembly, which are carried out directly, publicly, freely, confidentially, honestly and fairly within the Unitary State of the Republic of Indonesia based on Pancasila and the 1945 Constitution of the Republic of Indonesia The General Election Commission (KPU) is glue As election organizers, the Election Supervisory Body (Bawaslu) is an institution that oversees elections, but election success is not only the responsibility of the KPU or Bawaslu, but all elements of the Indonesian nation have their respective responsibilities and roles in holding successful elections, including the government. participating area. In holding General Elections, the Regional Government is mandated to provide assistance and facilities in accordance with statutory provisions. This study discusses the importance of the Regional Government's Role in the Implementation of General Elections.